Evaluating retail locations - Rogers, David (Henry Stewart Talks, 2009)
Importance of existing as well as new retail locations, How to analyze existing stores to provide insights in evaluating new locations, Key elements of a location study for a new store or shopping centre, Alternative methods for developing sales forecasts for proposed new locations